Quick preparative separation of natural naphthopyranones with antioxidant activity by high-speed counter-current chromatography - Leitão, Gilda G.; Leitão, Suzana G.; Vilegas, Wagner [UNESP] (My University, 2002)
The natural naphthopyranones paepalantine (1), paepalantine-9O-β-D-glucopyranoside (2) and paepalantine-9-O-β-D-allopyranosyl-(1→6)-O-β-D-glucopyranoside (3) were separated in a preparative scale from the ethanolic extract of the capitula of Paepalanthus bromelioides by high-speed counter-current chromatography (HSCCC). The solvent system used was composed of water-ethanol-ethyl acetate-hexane (10:4:10:4, v/v/v/v). This technique led to the separation of the three different naphthopyranone glycosides in pure form in approximately 7 hours. Paepalantine showed a good antioxidant activity when assayed by the DPPH radical spectrophotometric assay.
Keywords: Antioxidant Activity; High-Speed Counter-Current Chromatography; Naphthopyranone Glycosides; Antioxidants; Brazil; Chromatography, High Pressure Liquid; Chromatography, Thin Layer; Countercurrent Distribution; Eriocaulaceae; Ethanol; Free Radicals; Glycosides; Heterocyclic Compounds, 3-Ring; Naphthalenes; Plant Extracts; Pyrones; Paepalanthus